Aspectos epidemiológicos da tuberculose no estado do Pará, Brasil, no período de 2011 a 2021. - COSTA, Cosmo de Sousa (2025)
Introduction: The tuberculosis (TB) is an infectious disease that affect a million of people all over the world, including Brazil. Social factors, such as low income, poor housing conditions and comorbidities such as type ll diabetes, patient that living with HIV/AIDS are related to higher infection rates. Pará is a state that presents a high incidence of tuberculosis; therefore, it is essential to know the epidemiological aspects of the disease in the region. Objective: To describe epidemiological characteristics of TB cases reported in the state of Pará; to identify risk factors for TB; To analyze the temporal trend of tuberculosis cases. Methodology: Analysis of data available in official databases, such as the Notifiable Diseases Information System (SINAN/TABNET) registered during the period from January 2011 to December 2021. Analysis of the results by calculating the incidence rate, mean, median, standard deviation, Pearson’s Linear temporal correlation coefficient test, Chi-square and 95% confidence interval calculation (95% CI). As well as the elaboration of thematic maps made by QGIS. A statistical significance level of 0.05 was established. Results: Increased temporal trend of the incidence rate with moderate correlation (r=0.55). Higher concentration of cases in micro-regions with large population agglomerations, as well being male, black/brown, economically more productive age, with low schooling. In addition, there is an increasing temporal trend in the number of cases in the elderly and venerable populations such as persons deprived of liberty (PDL). Decreasing trend in adherence to treatment among newly diagnosed cases. Finally, as an outcome, there is a temporal increase in the number of cases that chose to abandon the treatment. Conclusion: In the analysis of the data, it was observed that the increase in the incidence rate is in line with the increase in the national average, especially from 2015 onwards, peaking in 2019. As well as an increase in the number of cases in the elderly. Thus, it is necessary to strengthen public policies aimed at primary care, as well as to amplify forms that seek to maximize the outcomes of cures and reduce dropout rates.